Landform influencing the morphology of the settlement amber - Mukherjee, Dipankar (Ahmedabad, 1994)
"Landform Influencing the Morphology of the Settlement" by Dipankar Mukherjee examines the intricate relationship between landforms and the development of human settlements. The book explores how various geographical features such as mountains, valleys, rivers, and plains shape the morphology of urban and rural areas. Mukherjee discusses the theoretical frameworks that explain these interactions, along with case studies that highlight specific settlements and their unique adaptations to their topographical conditions. The work emphasizes the importance of understanding landforms for urban planning and sustainable development, providing valuable insights for geographers, urban planners, and policymakers.
Keywords: Geography; Urban Planning; Landforms